2016
DOI: 10.1016/j.palaeo.2016.01.043
|View full text |Cite
|
Sign up to set email alerts
|

Multistratigraphic records of the Lower Cretaceous (Valanginian–Cenomanian) Puez key area in N. Italy

Abstract: We present a stratigraphic investigation of a Hauterivian to Cenomanian hemipelagic succession from Col Puez, in the Dolomites (Southern Alps, northern Italy). A composite section of seven segments was studied with bio-, magneto-, and chemostratigraphy, which enabled detailed and robust age calibration of the Puez succession. It also revealed the paleoceanographic history and helped identify the important global climatic events of that period. The age of the Lower Cretaceous Puez Formation in the Dolomites is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 136 publications
(208 reference statements)
1
3
0
Order By: Relevance
“…Organic nitrogen derives mostly from peptides and amino acids of planktonic organisms 61 and can therefore be used as an indicator for planktonic productivity. These data are comparable to modern data by 62 66 who showed that the distribution and abundance of N are correlated to TOC. Nitrogen availability often limits biological production, both in terrestrial and in marine environments.…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…Organic nitrogen derives mostly from peptides and amino acids of planktonic organisms 61 and can therefore be used as an indicator for planktonic productivity. These data are comparable to modern data by 62 66 who showed that the distribution and abundance of N are correlated to TOC. Nitrogen availability often limits biological production, both in terrestrial and in marine environments.…”
Section: Introductionsupporting
confidence: 90%
“…The grey-scale data (0 = black, max. 255 = white, no dimension) indicate relative brightness intensity and were obtained by scanning 26 polished rock samples on a flatbed scanner (Epson Perfection 4990 Photo; method in Lukeneder et al 66 , 77 ).…”
Section: Methodsmentioning
confidence: 99%
“…Climatic conditions in different periods of the Early Cretaceous seem to experience significant changes, especially a humid and stable climate that prevailed globally in the middle Early Cretaceous (Föllmi, 2012). The belemnite δ 18 O record of central Italy gradually evolved to a lighter value from early to late Hauterivian, and characterized by a minimum in the latest Hauterivian (Lukeneder et al, 2016). A similar trend occurs in the belemnite δ 18 O record of Hungary from the Hauterivian (Bodin et al, 2009; McArthur et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…These tests show that the interval of the series sampled at 0.1mis suitable for the recognition of the actual amplitude of the eccentricity cycles and thus viable for astronomical tuning.5.6. Origin of the cyclicities in the record The origin of the observed Milankovitch cyclicities in the measured proxy signals is most likely related to the variation in terrestrially-derived detrital input (e.g., Cotillon, 1987;Mutterlose and Ruffell, 1999;Reboulet et al, 2003;Sagasti, 2005;Martinez et al, 2015;Lukeneder et al, 2016). The intensification of the hydrological cycle typical during more humid periods is likely to correspond to an increase in detrital material.…”
Section: Impact Of the Sample Distance On The Cyclostratigraphic Intementioning
confidence: 99%